2002
DOI: 10.1354/vp.39-2-281
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Apocrine Sweat Gland Tumor of the Tail in a Cow

Abstract: A 4-year-old native-breed cow had a mass with wide areas of ulceration and hemorrhage at the base of the tail at the same level as the vulva. The tumor was 19 ϫ 13 ϫ 11 cm, appeared red-brown, and was firm to hard, with gritty areas apparent on cut surface. Histologically, the tumor mass was composed of multilayered epithelial cells forming glandular structures with occasional apical blebs and rare solidly packed cells in nests. The stroma included fibrous connective tissue, scattered or periglandular sheets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…CAM5.2, an antibody against CK8/9, is a reliable marker to detect glandular epithelia in dogs 11) . In the present case, as previously reported 8,12) , the luminal epithelial element was positive for pan-cytokeratin and CK8. In canine mammary gland tumors, biphasic proliferation is a frequently observed and characteristic feature.…”
Section: Discussionsupporting
confidence: 89%
“…CAM5.2, an antibody against CK8/9, is a reliable marker to detect glandular epithelia in dogs 11) . In the present case, as previously reported 8,12) , the luminal epithelial element was positive for pan-cytokeratin and CK8. In canine mammary gland tumors, biphasic proliferation is a frequently observed and characteristic feature.…”
Section: Discussionsupporting
confidence: 89%
“…The recent World Health Organization classification categorizes apocrine sweat gland tumors in domestic animals into adenoma/carcinoma, complex or mixed adenoma/carcinoma (or both), and ductal adenoma/ carcinoma [7][8][9] . Literature reviews showed the occurrence of mentioned tumor in other animal species as fallow, 3 mixed tumors on the ventral surface of the tail in cattle [10][11][12] , 2 cases each of adenoma and carcinoma in aged ponies [13] , 1 case of carcinoma in a golden hamster [14] and 1 case of apocrine adenoma in a hare [15] . Apocrine adenocarcinomas are also very rare in human [16] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also suggested that undifferentiated mesenchymal cells in the tumor tissue might play roles in the metaplasia in the mixed tumors 3) . Gulbahar et al 6) reported a case of mixed apocrine sweat gland tumor in a cow in which the mesenchymal elements were not immunopositive for SMA, suggesting that the metaplastic bone or cartilage might be derived from the undifferentiated stem cells rather than myoepithelial cells. In the present study, the spindle-shaped neoplastic cells adjacent to the chondroid matrix were not positive for SMA, suggesting that undifferentiated mesenchymal cells might be involved in the formation of chondroid matrix in this case.…”
Section: Discussionmentioning
confidence: 99%